Self-repairing capsule for low-calcium concrete and preparation method of self-repairing capsule
By using self-repair capsules containing metakaolin, sodium carbonate and other components in low-calcium concrete, the problems of slow crack repair efficiency and poor bonding of repair agents are solved, and fast and efficient crack repair and strength recovery are achieved.
Patent Information
- Application Number
- CN202411989212.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, the crack repair efficiency of low-calcium concrete is slow, and the repairing agent is not firmly bonded to the concrete substrate after filling the crack, resulting in the problem of new cracks.
A self-healing capsule including the capsule core and the capsule wall is used. The capsule core is composed of metakaolin, sodium carbonate, solid sodium silicate, water-absorbent resin and glucose. The capsule wall is composed of paraffin, polyethylene wax and ethanol. When the capsule breaks, the water-absorbent resin expands and flows out with the capsule core components. It combines alkaline exciter and water to generate N-A-S-H gel and calcium carbonate, fills the cracks and achieves firm bonding.
It has achieved rapid repair of cracks in low-calcium concrete, with high repair efficiency. The strength recovery rate can reach 104-106% after 7 days, and it is firmly bonded to low-calcium concrete after repair.
Smart Images

Figure CN119750950A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mortar, concrete or similar building materials, and particularly relates to a self-repairing capsule for low-calcium concrete and a preparation method thereof. Background Art
[0002] In today's energy-saving and emission-reduction environment, more and more studies are being conducted on using carbon dioxide to cure cement concrete products to achieve energy conservation and emission reduction. However, the carbonization reaction degree of ordinary silicate cement concrete with C3S as the main mineral component is low and its carbon fixation capacity is limited. To achieve the purpose of carbon dioxide curing cement concrete products, it is necessary to rely on low-calcium silicate minerals with strong carbon fixation capacity such as C3S2, CS, and γ-C2S. Therefore, low-calcium clinker with C3S2, CS, γ-C2S and other minerals as the main components came into being. Low-calcium concrete prepared with such low-calcium clinker can obtain excellent mechanical properties in a short time after using the carbon dioxide rapid curing process, greatly shortening the production process cycle. At the same time, the carbon fixation characteristics of low-calcium clinker are used to solidify carbon dioxide in concrete products, greatly reducing the carbon footprint of the cement industry.
[0003] After the low-calcium clinker reacts with carbon dioxide to form carbon dioxide reaction channels inside the concrete, which in turn form interconnected holes. Harmful media from the outside enter the concrete through these channels, destroying the internal structure and causing cracks inside the concrete. Nowadays, there are few reports on concrete self-repair capsules specifically for low-calcium concrete. Commonly used self-repair capsules are roughly divided into two categories: 1. Microbial repair capsules, which generate calcium carbonate precipitation through microorganisms to fill concrete cracks to achieve the purpose of repairing concrete; however, microbial capsules are limited by the survival rate of microorganisms. In some extreme environments, microorganisms are difficult to survive, resulting in a significant reduction in repair efficiency; for example, patent CN11108192B discloses a microbial self-repair capsule for marine concrete, which uses coral reef calcareous sand as a carrier of microorganisms to achieve the purpose of repairing concrete cracks by forming stable calcite. However, the patent does not take into account the impact of the marine environment on the survival rate of microorganisms, resulting in a significant reduction in repair efficiency; 2. Healing agent capsules, which achieve the purpose of repair by adding microcapsules containing liquid healing agents to concrete. When the concrete cracks, the microcapsules are destroyed, and the healing agent therein flows out and penetrates into the cracks under capillary action. After the healing agent is cured, the fracture surface is bonded together. Nowadays, most healing agent capsules are not early strength materials, and the repair time is long. At the same time, the healing agent and the concrete substrate are prone to problems such as poor bonding. For example, patent CN106747653A provides a self-repairing capsule, which has a relatively low repair efficiency and requires more than 3 days for complete repair. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a self-repairing capsule for low-calcium concrete and a preparation method thereof in view of the deficiencies in the prior art, so as to solve the problem that the efficiency of repairing cracks in low-calcium concrete is slow, and new cracks appear due to the poor adhesion of the repair agent to the concrete substrate after the repair agent is filled into the cracks.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A self-repairing capsule for low-calcium concrete comprises a capsule core and a capsule wall wrapped around the surface of the capsule core. The raw materials of the capsule core comprise, by weight, 60 to 100 parts of metakaolin, 20 to 40 parts of sodium carbonate, 10 to 20 parts of solid sodium silicate, 4 to 8 parts of water-absorbent resin (SAP), and 1 to 3 parts of glucose; the raw materials of the capsule wall consist of paraffin, polyethylene wax, and ethanol.
[0007] According to the above scheme, the average particle size of the metakaolin is 12.0-14.0 μm.
[0008] According to the above scheme, the modulus of the solid sodium silicate is 1.0 to 1.5.
[0009] According to the above solution, the water-absorbent resin is a polyacrylic acid salt water-absorbent resin.
[0010] According to the above scheme, the particle size of the capsule core is 1 to 10 mm, and the thickness of the capsule wall is 0.2 to 0.4 mm.
[0011] According to the above scheme, the mass ratio of the paraffin wax, polyethylene wax and ethanol is 1:0.1-0.2:5-5.5.
[0012] The present invention also includes a method for preparing the self-repairing capsule for low-calcium concrete, and the specific steps are as follows:
[0013] 1) Weigh the raw materials according to the proportion and set aside;
[0014] 2) uniformly mixing metakaolin, sodium carbonate, solid sodium silicate, water-absorbing resin and glucose, pre-pressing to obtain a repair agent powder, granulating the obtained repair agent powder with a granulator, sieving to obtain capsule core particles;
[0015] 3) paraffin wax, polyethylene wax and ethanol are mixed, heated and stirred to obtain a suspension, and then the obtained suspension is quickly sprayed on the surface of the rolling capsule core particles, and then dried and solidified at room temperature to obtain a self-repairing capsule for low-calcium concrete.
[0016] According to the above scheme, the pre-pressing pressure in step 2) is 1 to 5 MPa, and the pre-pressing time is 10 to 20 seconds.
[0017] According to the above scheme, the heating and stirring temperature in step 3) is 60-65°C.
[0018] The present invention also provides a self-repairing low-calcium concrete, which comprises low-calcium clinker and the self-repairing capsule, wherein the amount of the self-repairing capsule added is 1-5% of the mass of the low-calcium clinker.
[0019] Preferably, the raw materials and mass proportions of the self-repairing low-calcium concrete are as follows: low-calcium clinker 220-400 kg / m 3 , machine-made sand 800~1000kg / m 3 , 5-16mm crushed stone 400-600kg / m 3 , 16~31.5mm crushed stone 500~800kg / m 3 , water 110~200kg / m 3 , polycarboxylate water reducer 2.0~5.0kg / m 3 , the self-repairing capsules account for 1 to 5% of the mass of low-calcium clinker.
[0020] Low-calcium concrete is different from ordinary concrete. It has weak hydration ability, and its hydration products such as calcium hydroxide are much less than those of ordinary concrete. Therefore, some repair agents for ordinary concrete are not suitable for low-calcium concrete. The self-repairing capsule provided by the present invention is added to low-calcium concrete for use. When cracks appear in the low-calcium concrete, the capsule wall of the self-repairing capsule also breaks and enters the cracks. When external moisture enters the cracks, the water-absorbent resin absorbs water and expands, becomes liquid, and flows out with the remaining capsule core components of the repair agent and fills the gaps. The Al2O3·2SiO2 in the kaolin and the uncarbonized CaO·SiO2 in the low-calcium concrete react with alkaline activators such as solid sodium silicate and sodium carbonate and water to generate NASH gel and calcium carbonate. The reaction products begin to grow from the crack surface of the low-calcium concrete and gradually fill the entire gap. In this way, the bonding effect is more solid and the reaction is very rapid.
[0021] The repair efficiency is higher and can achieve the purpose of quickly repairing concrete.
[0022] In addition, the glucose used in the present invention can act as a binder, providing a certain cohesive force during the preparation of the capsule core, so that the capsule core can be cohesive during the pressing process, thereby avoiding the situation where it falls apart after being pressed. At the same time, glucose is also used as a calcium carbonate crystal phase conversion agent. In the process of reacting to generate calcium carbonate, it can induce the calcium carbonate crystal phase to be converted into needle-rod-shaped aragonite. The needle-rod-shaped aragonite is interwoven together to further improve the repair strength.
[0023] The beneficial effects of the present invention are as follows: 1. The self-repairing capsule provided by the present invention has a fast reaction rate and high repair efficiency, and the strength recovery rate after 7 days of repair can reach 104-106% at most, and the repaired capsule is firmly bonded to the low-calcium concrete. 2. The preparation method of the present invention has simple steps, low raw material cost, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a surface SEM image of the capsule core prepared in Example 1 of the present invention after simulating concrete repair reaction;
[0025] Figure 2 This is a surface SEM image of the capsule core prepared in Example 1 after simulating concrete repair reaction. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be fully and clearly described below in conjunction with embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A self-repairing capsule for low-calcium concrete comprises a capsule core and a capsule wall wrapped on the surface of the capsule core, and a preparation method thereof comprises the following steps:
[0029] Preparation of capsule core: 60 parts of metakaolin (average particle size 12.0-14.0 μm), 20 parts of sodium carbonate, 10 parts of solid sodium silicate (modulus 1.0), 4 parts of water-absorbent resin (polyacrylate water-absorbent resin, purchased from Shandong Linchuan Water Technology Co., Ltd.), and 1 part of glucose are mixed evenly, put into a press, and pre-pressed with a pressure of 5 MPa for 10 seconds to form tiny spherical particles to obtain a certain strength; then these tiny spherical particles are put into a disc granulator for granulation, sieved, and spherical capsule core particles with a particle size of less than 10 mm are obtained;
[0030] Preparation of self-healing capsule wall: paraffin wax, polyethylene wax and ethanol are weighed in a mass ratio of 1:0.1:5, stirred evenly at 60°C to obtain a suspension, and the suspension is quickly and evenly sprayed on the rolling capsule core particles using a high-pressure spray gun until a thin film with a thickness of 0.3±0.1 mm is formed on the surface of the capsule core. Then stop spraying and keep the capsule core rolling. Stop rolling after 5 minutes, collect and dry the particles to obtain a self-healing capsule.
[0031] Based on the self-repairing capsule prepared in this embodiment, the self-repairing low-calcium concrete is prepared. The components and their contents are as follows: low-calcium clinker (provided by Huaxin Cement Factory, the mineral composition and mass percentage of the low-calcium clinker are: CS: 12-18%, C3S2: 30-48%, C2S: 18-25%, the remainder is impurities, 45 μm sieve residue <15%, specific surface area of 500-550 m 3 / kg)380kg / m 3 , machine-made sand 900kg / m 3, 5~16mm crushed stone 400kg / m 3 , 16~31.5mm crushed stone 600kg / m 3 , water 160kg / m 3 , polycarboxylate water reducer 3.8kg / m 3 The self-repairing capsules prepared in this embodiment are 0, 3.8, 11.4, and 19 kg / m 3 (i.e., low-calcium clinker content of 0, 1%, 3%, 5%), and the fineness modulus of machine-made sand is 2.5. According to this ratio, four groups of concrete test blocks with a size of 100mm×100mm×100mm were prepared, with 3 in each group. After standard curing for 3 days, they were placed in a carbonization chamber and carbonized for 20 hours at a carbonization system of 30°C, 100% CO2 concentration, and 0.3MPa pressure to obtain four groups of low-calcium concrete test blocks.
[0032] Comparison of self-repair capsule repair efficiency: Each group of low-calcium concrete test blocks was divided into two groups. One group was directly pressed to the limit, and the second group was pressed to 80% of the limit value according to the limit pressure value of the first group. After being moved into the standard curing room for curing for 7 days, the strength test was conducted again to analyze and compare the repair rate of low-calcium concrete. The repair results are shown in Table 1:
[0033] Table 1
[0034]
[0035] Result analysis: It can be seen from Table 1 that the strength recovery rate of low-calcium concrete added with self-repairing capsules is higher than that of the group without self-repairing capsules, and with the increase of the amount of self-repairing capsules, the strength recovery rate also gradually increases, and even exceeds the original strength when the amount is 5%.
[0036] Take 10 capsule cores prepared in this example, the low-calcium concrete test block prepared in this example (the amount of self-repairing capsules is 3% of the mass of low-calcium clinker), and the powder (specific surface area of about 350m 2 / g, simulating the reaction that occurs when repairing in concrete) 50 parts and 30 parts of water, after mixing evenly, stir at a speed of 60r / min for 3 minutes, pour into a mold for molding, and measure its surface SEM image after curing at room temperature for 7 days. Figure 1 and Figure 2 As shown, it can be seen that the self-repairing reaction product includes needle-rod-shaped aragonite, which is intertwined with other reaction products to form a compact structure, making the repair effect better.
[0037] Example 2
[0038] A self-repairing capsule for low-calcium concrete comprises a capsule core and a capsule wall wrapped on the surface of the capsule core, and a preparation method thereof comprises the following steps:
[0039] Preparation of capsule core: 60 parts of metakaolin (average particle size 12.0-14.0 μm), 20 parts of sodium carbonate, 10 parts of solid sodium silicate (modulus 1.0), 4 parts of water-absorbent resin (polyacrylate water-absorbent resin), and 1 part of glucose are mixed evenly, put into a press, and pre-pressed at 5 MPa pressure for 10 seconds to form tiny spherical particles, then these tiny spherical particles are put into a disc granulator for granulation, sieved, and spherical capsule core particles with a particle size of less than 10 mm are obtained;
[0040] Preparation of self-healing capsule wall: paraffin wax, polyethylene wax and ethanol are weighed in a mass ratio of 1:0.1:5, stirred evenly at 60°C to obtain a suspension, and the suspension is quickly and evenly sprayed on the rolling capsule core particles using a high-pressure spray gun until a thin film with a thickness of 0.6±0.1 mm is formed on the surface of the capsule core. Then stop spraying and keep the capsule core rolling. Stop rolling after 5 minutes, collect and dry the particles to obtain a self-healing capsule.
[0041] Self-repairing low-calcium concrete was prepared based on the self-repairing capsules prepared in this example. Four groups of low-calcium concrete test blocks were prepared using the same method as in Example 1.
[0042] The repair rate of the prepared low-calcium concrete was tested using the same method as in Example 1. The repair results are shown in Table 2:
[0043] Table 2
[0044]
[0045] Results analysis: As shown in Table 2, the strength recovery rate of low-calcium concrete mixed with the self-repairing capsules prepared in this embodiment is higher than that of the group without self-repairing capsules, and the strength recovery rate gradually increases with the increase in the amount of self-repairing capsules. After the thickness of the self-repairing capsule wall is increased to 0.6±0.1mm in this embodiment, the repair efficiency is lower than 0.3±0.1mm. It may be that after the thickness of the capsule wall is increased, the capsule wall is more difficult to rupture, and the repair efficiency is reduced.
[0046] Example 3
[0047] A self-repairing capsule for low-calcium concrete comprises a capsule core and a capsule wall wrapped on the surface of the capsule core, and a preparation method thereof comprises the following steps:
[0048] Preparation of capsule core: 60 parts of metakaolin (average particle size 12.0-14.0 μm), 20 parts of sodium carbonate, 10 parts of solid sodium silicate (modulus 1.0), 4 parts of water-absorbent resin (polyacrylate water-absorbent resin), and 1 part of glucose are mixed evenly, put into a press, and pre-pressed at 5 MPa pressure for 10 seconds to form tiny spherical particles, then these tiny spherical particles are put into a disc granulator for granulation, sieved, and spherical capsule core particles with a particle size of less than 10 mm are obtained;
[0049] Preparation of self-healing capsule wall: paraffin wax, polyethylene wax and ethanol are weighed in a mass ratio of 1:0.2:5.5, stirred evenly at 60°C to obtain a suspension, and the suspension is quickly and evenly sprayed on the rolling capsule core particles using a high-pressure spray gun until a thin film with a thickness of 0.3±0.1 mm is formed on the surface of the capsule core. Then stop spraying and keep the capsule core rolling. Stop rolling after 5 minutes, collect, dry and solidify to obtain a self-healing capsule.
[0050] Self-repairing low-calcium concrete was prepared based on the self-repairing capsules prepared in this example. Four groups of low-calcium concrete test blocks were prepared using the same method as in Example 1.
[0051] The repair rate of the prepared low-calcium concrete was tested using the same method as in Example 1. The repair results are shown in Table 3:
[0052] Table 3
[0053]
[0054] Results analysis: As shown in Table 3, the strength recovery rate of low-calcium concrete mixed with the self-repairing capsules prepared in this embodiment is higher than that of the group without self-repairing capsules, and with the increase of the self-repairing capsule dosage, the strength recovery rate also gradually increases, and even exceeds the original strength at 5% dosage. After adjusting the proportion of the capsule wall, there is no obvious negative impact on the strength recovery.
[0055] Comparative Example 1
[0056] Concrete test blocks were prepared according to the mix ratio of the self-repairing low-calcium concrete in Example 1, except that the self-repairing capsules prepared in Example 1 were replaced with microbial self-repairing capsules of equal mass (prepared according to CN202110400525.4). The self-repairing capsule repair efficiency test was carried out using the method in Example 1, and the test results are shown in Table 4.
[0057] Table 4
[0058]
[0059] Result analysis: It can be seen from Tables 1-4 that the concrete repair efficiency of the microbial self-repair capsules used in the comparative example is significantly lower than the repair efficiency of the self-repair capsules prepared in the embodiment of the present invention.
[0060] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered within the protection scope of the present invention.
Claims
1. A self-repairing capsule for low-calcium concrete, characterized in that: The capsule comprises a capsule core and a capsule wall wrapped on the surface of the capsule core. The raw materials of the capsule core comprise, by weight, 60 to 100 parts of metakaolin, 20 to 40 parts of sodium carbonate, 10 to 20 parts of solid sodium silicate, 4 to 8 parts of water-absorbing resin, and 1 to 3 parts of glucose; the raw materials of the capsule wall are composed of paraffin, polyethylene wax and ethanol.
2. The self-repairing capsule for low-calcium concrete according to claim 1, characterized in that: The average particle size of the metakaolin is 12.0-14.0 μm; the modulus of the solid sodium silicate is 1.0-1.
5.
3. The self-repairing capsule for low-calcium concrete according to claim 1, characterized in that: The water-absorbent resin is a polyacrylic acid salt water-absorbent resin.
4. The self-repairing capsule for low-calcium concrete according to claim 1, characterized in that: The particle size of the capsule core is 1 to 10 mm, and the thickness of the capsule wall is 0.2 to 0.4 mm.
5. The self-repairing capsule for low-calcium concrete according to claim 1, characterized in that: The mass ratio of the paraffin wax, polyethylene wax and ethanol is 1:0.1-0.2:5-5.
5.
6. A method for preparing a self-repairing capsule for low-calcium concrete according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: 1) Weigh the raw materials according to the proportion and set aside; 2) uniformly mixing metakaolin, sodium carbonate, solid sodium silicate, water-absorbing resin and glucose, pre-pressing to obtain a repair agent powder, granulating the obtained repair agent powder with a granulator, sieving to obtain capsule core particles; 3) paraffin wax, polyethylene wax and ethanol are mixed, heated and stirred to obtain a suspension, and then the obtained suspension is quickly sprayed on the surface of the rolling capsule core particles, and then dried and solidified at room temperature to obtain a self-repairing capsule for low-calcium concrete.
7. The method for preparing the self-repairing capsule for low-calcium concrete according to claim 6, characterized in that: Step 2) The pre-pressing pressure is 1-5 MPa, and the pre-pressing time is 10-20 s.
8. The method for preparing the self-repairing capsule for low-calcium concrete according to claim 6, characterized in that: Step 3) The heating and stirring temperature is 60-65°C.
9. A self-repairing low-calcium concrete, characterized in that: The invention comprises low-calcium clinker and the self-repairing capsule according to any one of claims 1 to 5, wherein the amount of the self-repairing capsule added is 1 to 5% of the mass of the low-calcium clinker.
10. The self-repairing low-calcium concrete according to claim 9, characterized in that: The raw materials and mass proportions of the self-repairing low-calcium concrete are as follows: low-calcium clinker 220-400 kg / m 3 , machine-made sand 800~1000kg / m 3 , 5-16mm crushed stone 400-600kg / m 3 , 16~31.5mm crushed stone 500~800kg / m 3 , water 110~200kg / m 3 , polycarboxylate water reducer 2.0~5.0kg / m 3 , the self-repairing capsules account for 1 to 5% of the mass of low-calcium clinker.
Citation Information
Patent Citations
Single-component healing capsule and self-healing concrete
CN106747653A
Microbial microcapsules for self-healing of concrete cracks, their preparation method, and self-healing concrete.
CN113149511B
Microcapsule self-healing material which has easy-degradation capsule walls and is applied to fine cracks and micro cracks of concrete
CN110510910A
Mineral capsule for maritime work self-repairing concrete as well as preparation method and application of mineral capsule
CN118026574A
Self-healing material and preparation process thereof
US20150344365A1